Socio-Economic and Developmental Needs - Focus of Foresight Programmes - Attila Havas (Hungarian Academy of Sciences, Institute of Economics, 2003)
Emerging economies in the CEE/NIS region faced with a number of similar or same challenges when trying to find their new role in the changing international settings, while still characterised by their own distinct level of socio-economic development, set of institutions, culture and norms can benefit significantly from conducting foresight programmes. Yet, foresight should not be conducted for its own sake just because it is becoming fashionable throughout the world, and currently being promoted by the EU. On the contrary, there should be a strong link between foresight, decision preparation and policy-making. In other words, foresight should be used in the context of (adequately identified) policy needs. Its focus (e.g. purely technological, technoeconomic or broad socio-economic orientation) is, therefore, largely determined by the perceived socio-economic and developmental needs. Further, its focus, broad objectives, geographical scope (level), themes, time horizon, methods and participation are closely interrelated, and thus a careful but flexible project design is needed to assure coherence among these constituents. It should be borne in mind, however, that foresight is only one of the available policy instruments, and definitely not a panacea.
Keywords: 330